2018
DOI: 10.1001/jama.2018.7028
|View full text |Cite
|
Sign up to set email alerts
|

Association of Stress-Related Disorders With Subsequent Autoimmune Disease

Abstract: Psychiatric reactions to life stressors are common in the general population and may result in immune dysfunction. Whether such reactions contribute to the risk of autoimmune disease remains unclear. OBJECTIVE To determine whether there is an association between stress-related disorders and subsequent autoimmune disease. DESIGN, SETTING, AND PARTICIPANTS Population-and sibling-matched retrospective cohort study conducted in Sweden from January 1, 1981, to December 31, 2013. The cohort included 106 464 exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
210
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 286 publications
(256 citation statements)
references
References 33 publications
10
210
1
7
Order By: Relevance
“…Our subsequent gene set and pathway analyses provide some clues further implicating the immune system. Of note, these genetic results converge with evidence from epidemiologic cohort studies documenting the role of stressrelated disorders such as PTSD in autoimmune diseases, 49 case-control studies showing elevations of immune-related biomarkers in women with PTSD, 50,51 and epigenetic studies pointing to the role of the immune system in PTSD etiology. [52][53][54] Of note, it has been previously suggested that PTSD may be "a systemic disorder rather than one confined to the mind".…”
Section: Discussionsupporting
confidence: 61%
“…Our subsequent gene set and pathway analyses provide some clues further implicating the immune system. Of note, these genetic results converge with evidence from epidemiologic cohort studies documenting the role of stressrelated disorders such as PTSD in autoimmune diseases, 49 case-control studies showing elevations of immune-related biomarkers in women with PTSD, 50,51 and epigenetic studies pointing to the role of the immune system in PTSD etiology. [52][53][54] Of note, it has been previously suggested that PTSD may be "a systemic disorder rather than one confined to the mind".…”
Section: Discussionsupporting
confidence: 61%
“…Notably, rs6906714 is also an expression QTL for several genes including PSORS1C1 and PSORS1C2, which are psoriasis susceptibility genes that are expressed in thyroid tissue (Table S2). Genes associated with autoimmune disorders have been previously associated with PTSD(50); the overlap between stress disorders and immune/inflammatory disorders is an ongoing area of research (51). We also observed an interaction of rs6906714 with childhood trauma in the discovery cohort, and of rs6906714 with lifetime PTSD in the replication cohort, which is consistent with neuropsychiatric responses to stress that show increased risk of subsequent autoimmune disease (Figure 2)(51).…”
Section: Discussionsupporting
confidence: 82%
“…Although the specific molecular mechanisms by which SSRIs exert such effects are not clear, a variety of mechanisms have been proposed, including those mediated by the serotonin transporter, mediated by NF‐κB, by IL‐10, and via actions on cyclic adenosine monophosphate signaling . Supporting this, a recent large‐scale epidemiological study reported that persistent use of SSRIs during the first year after PTSD diagnosis was associated with attenuated risk of autoimmune disease . Moreover, chronic PTSD patients who received SSRIs showed significant reduction in both clinical symptoms and serum IL‐1β levels .…”
Section: Potential Anti‐inflammatory Treatment Strategiesmentioning
confidence: 86%
“…In addition to these classic psychobehavioral features, physical morbidities, such as obesity, diabetes, and metabolic syndrome, are common in individuals with PTSD . Moreover, epidemiological studies have found a link between PTSD and an increased risk of serious physical diseases, such as cardiovascular disease and autoimmune disease . As these diseases have an inflammatory component, it is suggested that the immune system is dysregulated in PTSD.…”
mentioning
confidence: 99%